Analisis Komponen Makna Tipe-Tipe Semantik Verba “Menyakiti” dalam Bahasa Jawa - Rahayu, Yayuk Eny; Sawardi, Sawardi (ppjbsip, 2022)
This study aims to describe: (1) the classification of the components of the meaning of the verb